Transparency of literary onomastics in the situation of foreign language reception - Bayanbayeva, Ж.А.; Tattimbetova, К.О.; Lomova, Е.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article examines the specifics of the perception of a literary onomasticon in the coordinates of a foreign cultural and national tradition. Theoretical works in the field of onomastics were used as a methodological basis. The relevance of the chosen topic is determined by the fact that onomastics is included in the system of pragmatic and syntagmatic relations in the structure of the artistic context and is designed for an adequate level of reader perception. The novelty of the research consists in an attempt to systematize a range of problems related to the semantic, stylistic and emotive relevance of the onomasticon of original and translated texts. It is proved that in the space of foreign language culture, mentality, a folklore name, like the name of a fabulous literary character, loses its versatility, and informative capacity. The problem is partly solved by substitute translation or intra-phrasal commentary. It is concluded that the successful solution to the problem of transparency of literary onomastics is associated with the need for a thorough analysis of the original text and with finding the closest correspondences in the mental, linguistic and socio-cultural orientation of the foreign-speaking recipient.